استخدام تقانة الذكاء الاصطناعي في إعادة هندسة العمليات : بالتطبيق في الشركة العامة لصناعة الادوية و المستلزمات الطبية في نينوى - د. صباح انور يعقوب (PROSPECTIVE RESEARCHES, 2023)
This research aims at explaining the importance of using Artificial Intelligence (AI) and operations re- engineering in The State Company for Drugs Industries and Medical Appliances in Nineveh. The research depended on collecting the opinions of a selected sample of managers in the company under study. The number of Managers was (50) at different levels of management (the high, intermediate and the executive levels) in the company. The opinions were collected through distributing questioneer forms prepared for this purpose. The Research has proved that there is a significant relationship between (AI) and operations Re- engineering. The research used anumber of statistical methods In order to find the relationships between the two variables.